Методология создания математической модели одновального двигателя ГТЭ-45(60А) - Аннопольская, И. Е.; Коваль, В. А.; Романов, В. В.; Тарелин, А. А. (НТУ "ХПИ", 2008)
The new approach, statement and methods of implementation of a problem of identification of parameters and characteristics of mathematical models of various circuit design of the power gas-turbine engine on experimental data is observed. The problem is solved in uniform informational space by means of modern mathematical methods of search of an optimum.
Keywords: газотурбинные двигатели; идентификация математической модели; испытания двигателя; метод Нелдера-Мида; методы многокритериальной оптимизации; дроссельная характеристика